The utility of low-iodine diet in preparation for thyroid cancer therapy with radioactive iodine-A cohort study - Hongxiu Luo; Hongxiu Luo; Andrew Tobey; Sungyoung Auh; Craig Cochran; Noha Behairy; Maria Merino; Marina Zemskova; Joanna Klubo-Gwiezdzinska (Frontiers Media S.A., 2022)
Objective: A low-iodine diet (LID) of <50μ iodine/day is recommended as preparation for radioactive iodine (RAI) therapy in patients with differentiated thyroid cancer (DTC). The 24-h urinary iodine excretion (UIE) is utilized to evaluate the iodine-depleted status. The aim of this study was to test the association between UIE and progression-free survival (PFS).Patients and methods: In total, 70 patients with intermediate- or high-risk DTC, post-total thyroidectomy, adhered to 2 weeks of LID and had UIE measured before RAI therapy. A Cox regression model was performed to study the contribution of UIE to PFS.Results: The study group consisted of 68% (48/70) of women, aged 41.5 [IQR 31.0, 54.0] years, with tumor size 2.8 [IQR 1.8-4.5] cm, and presence of distant metastases in 22.9% (16/70) of patients. Patients were treated with 1-5 RAI dosages with the median cumulative activity of 150 [IQR 102-314] mCi (5.5 [IQR 3.8-11.6] GBq). During the follow-up of 3.7 [IQR 1.5-6.5] years, 21.4% (15/70) of patients had disease progression. The risk of progression was significantly higher in patients with UIE ≥200 µg/day at the time of RAI administration than in those with UIE <200 µg/day (HR 3.35, 95% CI 1.09-10.34, and p = 0.02). However, the multivariate Cox proportional hazards regression analysis adjusted for age, tumor size, and presence of distant metastases suggested that only distant metastases were independently significantly associated with the risk of progression (HR 5.80 (1.17-28.67), p = 0.03).Conclusions: Although UIE ≥200 µg/day might be associated with worse PFS in RAI-treated DTC patients, the presence of distant metastases is a strong independent predictor of progression. Less stringent LID might be sufficient to achieve a UIE of <200 µg/day.